LANGUAGE AND STYLE FEATURES IN KARAKALPAK CHILDREN’S PROSE(Example of A. Abdiyev’s works) (SCIENCE and SOCIETY, 2026)
The article examines the linguistic and stylistic features of Karakalpak children’s prose based on the works of A. Abdiev. It analyzes the author’s narrative techniques, the role of the narrator, and the use of dialogue and monologue. Special attention is paid to the adaptation of language to children’s psychology. The study highlights the educational and aesthetic significance of children’s prose.